THE CRISIS OF ISLAMIC HISTORICAL EXEMPLIFICATION AND THE REACTUALIZATION OF ZAKAT VALUES IN SHAPING THE MORALITY OF THE MODERN YOUNG GENERATION - Suhaimi; Ali Akbar; Bambang Wahyu Susanto (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the crisis of Islamic historical exemplary among the younger generation in the digital era and examine the reactualization of zakat values as a strategy for moral formation within the framework of Islamic moral education. This research employs a qualitative approach based on literature studies by analyzing books, scientific journals, academic publications, and relevant documents using content analysis and contextual interpretation. The findings reveal that the crisis of Islamic historical exemplary is closely related to the weakening of moral references among the younger generation due to the dominance of digital culture, individualistic lifestyles, and the declining role of family and educational institutions in internalizing Islamic values. The study also indicates that Islamic historical exemplary functions pedagogically in shaping moral imagination, ethical judgment, identity formation, and behavioral habituation among youth. Meanwhile, zakat is not merely positioned as a ritual obligation, but as a form of social education that instills solidarity, empathy, collective responsibility, and social awareness. The integration of Islamic historical exemplary and zakat-based social practices forms an integrative model of Islamic moral education that combines value internalization with practical social engagement.  This study emphasizes the importance of revitalizing Islamic historical exemplary and actualizing zakat values in order to strengthen youth morality in the digital era. However, this research is limited to a conceptual literature study and has not yet involved empirical field data regarding the implementation of integrative moral education practices in schools or Muslim communities. This study offers a new perspective on Islamic moral education by integrating the pedagogical function of Islamic historical exemplary with zakat-based social practices as a contextual strategy for shaping the moral character of the younger generation in contemporary digital society.